Assistência ao paciente com infarto agudo do miocárdio com supradesnivelamento de segmento ST em um município brasileiro: impacto após implementação do serviço de telecardiologia - Oliveira, Maria Letícia de França (2023)
Introduction: Cardiovascular diseases (CVD) are the main causes of death in Brazil for more than 50 years, and the largest portion attributable to coronary artery disease (CAD), which comprises a wide spectrum of clinical conditions. Regarding acute coronary syndromes (ACS), an acute ST-elevation myocardial infarction (STEMI) is responsible for the highest mortality rates, up to 17.2% in some Brazilian regions. Objective: To evaluate the impact on the care of patients with STEMI admitted to the Hospital Universitário de Lagarto (HUL), from the implementation of the Telecardiology (TCL) service in the State of Sergipe, in the period of August 2021 to July 2022. Methodology: This is an observational, retrospective and longitudinal study, with data collected from the SAMU-Sergipe, from the Hospital de Cirurgia, from the Angiocor, from the State Health Department, and from HUL. The characterization of the sample was performed by a descriptive analysis of categorical and quantitative data. Results: Between August 2021 and July 2022, 41 patients admitted to HUL had the diagnosis of STEMI and were regulated by TCL, with a mean age of 61.8 years and 78% male. Among the comorbidities, 78% were hypertensive and 58.5%, diabetic. Regarding the clinical condition of admission, 85.3% reported typical chest pain, 29.2% nausea/vomiting and 19.5% dyspnea. At electrocardiogram, the myocardial wall most affected by infarction was the inferior wall (36.3%), followed by the anterior wall (20.4%). The rate of patients referred to perform primary percutaneous coronary intervention was 65.8%, with average time between arrival at the hospital of origin until angioplasty (door-balloon time) of 06h 47min. The rate of thrombolysis was 22%, with an average time between arrival at the hospital of origin and beginning of infusion of the thrombolytic (door-needle time) of 01h 57min. At the end of the first 30 days since the diagnosis of STEMI, the mortality rate was 13.16%. Conclusion: From the implementation of the TCL service in the state of Sergipe, it is remarkable the improvements in some points of the line of care of patients with STEMI from the city of Lagarto/SE. It is essential to promote the continuing education of professionals and the application of chest pain protocols to continue in search of better clinical care for these patients.